2005
DOI: 10.1093/deafed/eni004
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and Coping Strategies among Deaf Students

Abstract: Research studies on the determinants of self-esteem of deaf individuals often yield inconsistent findings. The current study assessed the effects on self-esteem of factors related to deafness, such as the means of communication at home and severity of hearing loss with hearing aid, as well as the coping styles that deaf people adopt to cope with everyday life in a hearing world. Data were collected among the deaf students of California State University, Northridge. Hierarchical regression modeling showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 40 publications
3
82
0
7
Order By: Relevance
“…Accordingly, a variety of studies has found deaf youth to report greater self-confidence and social well-being after receiving CIs (e.g., Dammeyer, 2010;Hilton, Jones, Harmon, & Cropper, 2013;Jambor & Elliott, 2005;Leigh, Maxwell-McCaw, Bat-Chava, & Christiansen, 2009;Wheeler, Archbold, Gregory & Skipp, 2007). As Archbold (2015) and others have indicated, however, the situation is complicated.…”
Section: Social Maturity Among Deaf Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a variety of studies has found deaf youth to report greater self-confidence and social well-being after receiving CIs (e.g., Dammeyer, 2010;Hilton, Jones, Harmon, & Cropper, 2013;Jambor & Elliott, 2005;Leigh, Maxwell-McCaw, Bat-Chava, & Christiansen, 2009;Wheeler, Archbold, Gregory & Skipp, 2007). As Archbold (2015) and others have indicated, however, the situation is complicated.…”
Section: Social Maturity Among Deaf Learnersmentioning
confidence: 99%
“…This is especially true among older students and young adults for whom the language demands are greater and the contexts of language and social interaction associated with social maturity are more abstract and complex (Dammeyer, 2010;Hilton et al, 2013). Knutson, Boyd, Reid, Mayne, and Fetrow (1997), Bat-Chava and Deignan (2001), Jambor and Elliott (2005), and Wheeler et al (2007) thus found that although deaf youth reported improved communication with hearing peers after receiving CIs, relatively few children, those with the best speech and hearing, were fully accepted by hearing peers. Moores and Kluwin (1986) argued that social maturity, and not just academic achievement, should be considered in decisions about educational placement of deaf students in mainstream or separate classrooms.…”
Section: Social Maturity Among Deaf Learnersmentioning
confidence: 99%
“…24 However, deafness and hearing loss can have a profound effect on individuals and have been associated with a range of negative consequences, including educational and employment disadvantages, social isolation and stigmatisation. 25,26 According to a report by the World Health Organization, hearing loss is the second leading cause globally of 'years lived with disability' and has a larger non-fatal burden than alcohol use disorders.…”
Section: Impact Of Hearing Lossmentioning
confidence: 99%
“…Deafness present at birth or during early childhood (the pre-lingual period) has considerable effects on speech acquisition and cognitive and psychosocial development. 27 Deafness acquired post-lingually requires the individual to adopt new communication strategies and often an entirely different lifestyle, 24 and can result in isolation and compromised quality of life (QoL). 27 Hearing loss affects not only individuals, but also the people around them such as family and co-workers.…”
Section: Impact Of Hearing Lossmentioning
confidence: 99%
“…Nevertheless, researchers have asserted that there is a HH identity (Andersson and Lawenius 1997), an identity that young people may construct 'based on their position with regard to hearing and deaf peers, and the differentness of both groups' (Israelite, Ower, and Goldstein 2002, 144). A study of the self-esteem of deaf students showed that identification with similar others has a positive impact on the individual's self-esteem, even when the identification is with a devalued minority group (Jambor and Elliot 2005).…”
Section: Identity and Self-esteemmentioning
confidence: 99%